Influence of accommodation on the academic performance of architecture students / Joy Joshua Maina and Joshua Yavini Aji - Maina, Joy Joshua; Aji, Joshua Yavini (Faculty of Architecture, Planning and Surveying, 2017)
Academic performance of students in Higher Education is an issue of concern following rising global unemployment rates and funding problems because of its link to social and economic progress for many countries. This study investigates the influence of accommodation as a subset of school factors on academic performance of HE students employing students from Ahmadu Bello University (ABU) Zaria, the oldest school of Architecture in Nigeria. Questionnaires from 96 respondents were analyzed for Relative Influence Index, differences in ratings of 24 variables via Mann Whitney U test and Kendall Tau test for possible relationships of academic performance with room size. Results reveal living conditions notably cleanliness, electricity and water supply, overpopulation and territoriality most influence academic performance. Students living on campus also perform better academically and room size significantly influenced academic performance. The study recommends, amongst others, that policy makers and facility managers prioritize current management practices to improve living conditions in existing accommodation facilities on campus while planning for adequate infrastructure to cater for student accommodation needs in future.